Comparative evaluation of daily rhythm of urinary excretion in Equus caballus and Bos taurus by means of fractional clearance. Issue 6 (2nd November 2019) - Arfuso, Francesca; Giannetto, Claudia; Giudice, Elisabetta; Rizzo, Maria; Panzera, Michele; Piccione, Giuseppe
ABSTRACT: The aim of this study was to evaluate the daily variations of urinary excretion of the main electrolytes in Equus caballus and Bos taurus maintained under natural photoperiod. Animals were housed in individual indoor stalls under natural conditions. Urine and blood samples were taken from all the subjects every 4 h for 24 h period and were analyzed to assess the creatinine, calcium, phosphorus, magnesium, and chloride concentration. The fractional excretions of Na (%CrNa), K (%CrK), Cl (%CrCl), P (%CrP), Ca (%CrCa), and Mg (%CrMg) were calculated. Daily oscillations with nighttime acrophases of %CrNa, %CrK, and %CrCl are observed in horse; the acrophases of the parameters which resulted periodic in cow, including %CrNa, %CrCa, and %CrMg, are verified during the light phase. This study brings a contribution to the knowledge of the periodic phenomenon of the urinary excretion in the equine and bovine species. The results suggest that horse and cow are characterized by different circadian patterns for renal fractional clearance and that in these species, in addition to the external circadian stimuli, the renal excretion rhythms are also controlled by a self-sustained intrinsic renal clock that contribute to define the temporal patterns (daytime and nighttime).